TEACHING ENGLISH PRONUNCIATION THROUGH SONGS - Abdusalimova Ruxshona; Zulfiya Axmedova (TADQIQOTLAR, 2026)
Annotation: In recent years, the importance of effective pronunciation in learning English as a foreign language has gained significant attention. Pronunciation plays a crucial role in communication, as it directly affects learners’ ability to be understood and to understand others. Despite its importance, many learners face difficulties in mastering English pronunciation due to differences between their native language and English sound systems. Traditional methods of teaching pronunciation often focus on repetition, drills, and isolated sound practice, which can be monotonous and less engaging for students. As a result, there is a growing need for more interactive and motivating approaches in language classrooms. One such innovative method is the use of songs as a teaching tool. Songs provide authentic language input, natural rhythm, stress, and intonation patterns, making them an effective resource for improving pronunciation. Through listening and singing along, learners can develop better phonetic awareness, improve their listening skills, and internalize correct pronunciation in an enjoyable way. Moreover, songs create a relaxed and positive learning environment, which reduces anxiety and increases students’ motivation. This article aims to explore the effectiveness of teaching English pronunciation through songs, highlighting its benefits, practical techniques, and its impact on learners’ pronunciation skills.